PENGEMBANGAN KERANGKA SISTEM PELATIHAN BERBASIS KOMPETENS I SECARA DARING UNTUK PERSIAPAN UJI KOMPETENSI RUMPUN ILMU KOMPUTER - Yeni, Refliza; Febriani, Yeza; Djusar, Syahtriatna; Fajrizal; Van FC, Lucky Lhaura; Afriansyah; Wiza, Fana (Universitas Lancang Kuning, 2023)
The success of the digital digitization process is influenced by various factors, including the competence of national human resources in the digital field. Learning or training activities to increase competency as a preparation for potential competency test participants, cannot be included in a formal learning activity, because in a training, participants come from various diverse backgrounds, will have various obstacles and problems in participating in formal learning or training. Development of an online training system framework that can be used to improve the competence of prospective workers or competency test participants at a training institution or institution where competency tests are held, especially in the field of computer science. The framework structure developed includes: a) Determination of competency unit achievements in accordance with the competency test scheme to be followed, b) Online presentation of material divided into competency units, c) Initial self-assessment, d) Online independent learning, e) Discussion and f) Final independent assessment. In addition to developing the framework, an online training application was also developed as a tool in the implementation of the developed training system framework. The practicality test results for using the application for 33 respondents were an average percentage of 91%. The effectiveness value obtained after carrying out the initial independent assessment for 18 experimental class participants was: 48% competent, and became 94% in the final assessment